Liberados por el perdón, pero atados por la promesa - Escríbar Wicks, Ana (Cuadernos Judaicos, 2011)
This work examines the relationship between forgiveness, memory and forgetfulness; it analyzes the use and possible abuse of the two last ones and the connection that exists between promise and forgiveness. The thought of Paul Ricoeur and Hannah Arendt in respect to these matters contributes the criterions used for those revision and analysis. The exposition ends with a brief comparative study of the statements of both authors.